Chromosomal rearrangements during vegetative growth of a wild strain of Saccharomyces cerevisiae. - Longo, E (1993)
Electrophoretic karyotypes of two strains of Saccharomyces cerevisiae, a haploid laboratory strain and a wild strain known to be at least diploid, have been checked during vegetative growth. The karyotype of the haploid strain was very stable; however, the diploid strain underwent frequent modifications. In most cases the number of bands was reduced, but occasionally we observed one band splitting into two. In one case, chromosomal rearrangements took place between differently sized copies of chromosomes I and VI. We concluded that the chromosome length polymorphism observed among wild strains of S. cerevisiae could be explained partly by chromosomal structure reorganization occurring during mitosis.